Manfaat Senam Ergonomik Dalam Penurunan Tekanan Darah (Hipertensi) Pada Lansia : Scoping Review - Tondok, Santalia Banne; Swastika, I Ketut; Simanjuntak, Roganda (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Aging is a natural part of human life. Aging is one of the factors that cause hypertension, as with increasing age, bodily functions decline, marked by a decrease in the elasticity of arterial blood vessels and increased stiffness of blood vessels, making them more susceptible to elevated blood pressure in the elderly. Blood pressure is one of the vital signs, along with respiratory rate, heart rate, oxygen saturation, and body temperature. One of the common issues related to blood pressure is hypertension, which contributes to premature mortality worldwide. A person is considered to have hypertension if their systolic blood pressure is > 140 mmHg and diastolic blood pressure is > 90 mmHg. From a health perspective, as we age, we become more vulnerable to various physical, mental, social, and economic issues. High blood pressure not only affects your quality of life but can also be life-threatening. Lack of attention to lifestyle factors, such as poor dietary habits or insufficient physical activity, can contribute to the development of high blood pressure in the elderly. To prevent the risk of more severe complications, blood pressure can be controlled by changing lifestyle habits and engaging in regular physical activity, one of which is ergonomic exercise, which is very practical, efficient, and easy to perform. This literature review aims to analyze the application of ergonomic exercise in lowering blood pressure in hypertensive patients. Based on several reviews of various articles, it is evident that the application of ergonomic exercise has proven effective in lowering blood pressure in hypertensive patients.